2007
DOI: 10.1086/511679
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in HIV-Infected Patients from an Urban, Midwestern US Outpatient Population

Abstract: The prevalence of metabolic syndrome is high among HIV-infected persons, but not higher than the prevalence among HIV-uninfected persons. Traditional risk factors play a more significant role in the development of metabolic syndrome than do HIV treatment-associated factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
175
4
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(206 citation statements)
references
References 30 publications
21
175
4
6
Order By: Relevance
“…In our study we have found increase in total cholesterol, triglyceride, LDL, VLDL which is consistent with previous study done by Buchacz et al 13 Mondy et al has reported increased level of triglyceride which is consistent with our finding but they reported low levels of total cholesterol and LDL. 12 In present study HDL was low and this is consistent with other studies by Pariad et al, Buchacz et al, Khiangte et al, Mondy et al and G Shor Posner et al [10][11][12][13]25 Khiangte et al showed deranged lipid profile in their HIV patients and in them LDL levels decreased as CD4 count decreased which is consistent with our observation. However LDL decreases while triglyceride and VLDL increases with decrease in CD4 count in their study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study we have found increase in total cholesterol, triglyceride, LDL, VLDL which is consistent with previous study done by Buchacz et al 13 Mondy et al has reported increased level of triglyceride which is consistent with our finding but they reported low levels of total cholesterol and LDL. 12 In present study HDL was low and this is consistent with other studies by Pariad et al, Buchacz et al, Khiangte et al, Mondy et al and G Shor Posner et al [10][11][12][13]25 Khiangte et al showed deranged lipid profile in their HIV patients and in them LDL levels decreased as CD4 count decreased which is consistent with our observation. However LDL decreases while triglyceride and VLDL increases with decrease in CD4 count in their study.…”
Section: Discussionsupporting
confidence: 93%
“…10,11 Various studies have shown different prevalence and pattern of dyslipidaemia. [10][11][12][13] Infection can increase serum triglyceride (TG) level by decreasing the clearance of circulating lipoprotein, which thought to be due to reduced lipoprotein lipase or by stimulating lipid synthesis in liver through increase in either hepatic fatty acid synthesis or re-esterification of fatty acid derived from lipolysis. 14 Multiple pathogenic mechanisms by which HIV virus leads to dyslipidaemia have been hypothesized but they are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…estimaram que 30% dos adultos em uma área rural do Nordeste brasileiro (não infectados por HIV, idade média 49 anos) fossem portadores de SM, pelos critérios do NCEP-ATPIII (28 (8). A nosso ver, as discrepâncias entre os resultados dos diversos estudos não permitem, ainda, concluir se há aumento do risco de SM entre indivíduos com HIV, mas esse risco não parece estar associado à TARV ou à duração da infecção (8,31).…”
Section: Diehl Et Alunclassified
“…Related to this, abdominal obesity as a typically morphological abnormality has been observed among both HIV-positive men and women (Galli et al, 2003;Jaime et al, 2006) in many countries where HAART has been available for a long time. Two recent studies showed that 45.7% (n= 223) of Brazilian HIV+ (Jaime et al, 2006) and 30.7% (n=471) of American HIV infected subjects (Mondy et al, 2007) had central obesity.…”
Section: Introductionmentioning
confidence: 99%